The retail market for fresh and dry beans in Uganda : An investigation of cultivars in prices and implications for breeders - Grisley, B.; Mwesigwa, D. (International Center for Tropical Agriculture, 1990)
Twelve consumer retail markets in Uganda were studied 1998 in March and June of 1990 to determine the fresh and dry bean cultivars offered and to determine factors that explain variation in market prices. A total of 33 cultivars were offered in March and 30 in June in both the fresh and dry form. Kanyabwa and Nambale were the most frequently occurring cultivars. The revenue advantage of fresh over dry beans ranged from 30 to 279 percent across the cultivars sold. Farmers thus have a revenue incentive to supply fresh beans. Markets external to Kampala had significantly lower fresh, but not dry bean prices than Kampala markets. The bean grain characteristics size and color were not significant in explaining price variability. The implication for bean breeders in Uganda is that size should not be an important criterion for in a selection program and color should only be used when in conjunction with geographical area. The overall results suggest that preferences for beans, as reflected by consumer-prices paid, are a function of taste and grain size and color were not strong indicators or proxies of taste